Language Typology Trace Based on Motion Events: Javanese Spoken by English Learners - Lestiono, Riski; ., . (International Journal of Engineering and Technology, 2019)
This study aimed at identifying the ways Javanese, one of Austronesian languages, speakers expressed motion events, either using manner-incorporating sentences, path-incorporating sentences, or equipollently framing manner and path in the same predication position. The investigated speakers were English learners. Furthermore, the study investigated whether language contact played a role in the language change. After analyzing data from Javanese speakers learning English, it was revealed that Javanese consultants used mostly manner verbs, behaving more like a satellite-framed language, no longer an equipollently-framed. Language contact played a role in the tendency alteration of Javanese speakers to produce manner verbs in the predicate position caused by their learning English, which is a satellite-framed language with major construction of manner-incorporating sentences. The result of the study on language typology of Javanese spoken by English learners could end up showing that language contact in the multilingual contexts might contribute to any language variation. Â Â